Structured Shared Spaces as a Basis for Building Business Process Support Systems: A Generic Model and Analysis of Examples - Bider, Ilia; Johannesson, Paul; Perjons, Erik (Complex Systems Informatics and Modeling Quarterly, 2018)
Though the concept of shared spaces had been known in Groupware and Computer Supported Cooperative Work (CSCW) for quite a while, it did not become popular until the arrival of the Internet and social software. Implicitly, the concept of shared spaces has penetrated many IT-areas, including the area of Business Process Management. Though shared spaces are used in many systems and tools, like Google Drive and Projectplace, there is a lack of research investigating this usage in a generic way. The article aims to fill this gap by introducing a generic model of a Business Process Support (BPS) system based on shared space that supports the comparison, analysis and design of BPS systems. In addition, the article goes in more details on one design issue – the structuring of shared spaces. This is done by analyzing and comparing two different BPS systems that exploit the concept of shared spaces, though implicitly. These systems use different approaches to shared space structuring. The first one organizes the information by grouping similar types of items without regard to the flow of activities in a business process, while the other organizes the information around groups of activities that are usually completed as a block. Which model to choose in a particular situation depends on the characteristics of the business process and its participants. In order to facilitate this choice, the article offers a number of guidelines derived from the experience of using the two BPS systems in practice. The article also discusses in what circumstances BPS systems with shared spaces are preferable to traditional workflow BPS systems.